Purification and characterization of 31-kDa palm pollen glycoprotein (Ela g Bd 31 K), which is recognized by IgE from palm pollinosis patients - Kimura, Yoshinobu; Maeda, Megumi; Kimura, Mariko; Lai, Oi Ming; Tan, Siang Hee; Hon, Sook Mei; Chew, Fook Tim (Oxford University Press (OUP), 2002)
A basic glycoprotein, which was recognized by IgE from oil palm pollinosis patients, has been purified from oil palm pollen (Elaeis guineensis Jacq.), which is a strong allergen and causes severe pollinosis in Malaysia and Singapore. Soluble proteins were extracted from defatted palm pollen with both Tris-HCl buffer (pH 7.8) and Na-acetate buffer (pH 4.0). The allergenic glycoprotein was purified from the total extract to homogeneity with 0.4% yield by a combination of DEAE- and CM-cellulose, SP-HPLC, and gel filtration. The purified oil palm pollen glycoprotein with molecular mass of 31 kDa was recognized by the β1-2 xylose specific antibody, suggesting this basic glycoprotein bears plant complex type N-glycan(s). The palm pollen basic glycoprotein, designated Ela g Bd 31 K, was recognized by IgE of palm pollinosis patients, suggesting Ela g Bd 31 K should be one of the palm pollen allergens. The preliminary structural analysis of N-glycans linked to glycoproteins of palm pollens showed that the antigenic N-glycans having α1-3 fucose and β1-2 xylose residues (GlcNAc2∼0Man3Xyl1Fuc1∼0GlcNAc2) actually occur on the palm pollen glycoproteins, in addition to the high-mannose type structures (Man9∼5GlcNAc2).